2013
DOI: 10.14430/arctic4289
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Perceptions of Current Planning, Assessment and Science Initiatives in Canada’s Beaufort Sea

Abstract: ABSTRACT. Over the past 30 years, the Beaufort Sea has been the site of many regional studies and planning efforts. Currently, three major initiatives are underway: the Integrated Regional Impact Study, which focuses on science; the Integrated Ocean Management Plan; and the Beaufort Regional Environmental Assessment. Despite the mounting pressures for offshore energy development in the region, little attention has been given to whether these initiatives facilitate a more coordinated and informed approach to pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…But this is not unique to the Nunavut's regulatory process. A lack of institutional, community and research capacities in the Arctic (and many other locales) have been identified as limiting factors to meaningful stakeholder and community participation (Fidler & Noble, 2013;McCrank, 2008), and to adaptive management more broadly (Stratos, 2017). Through terms and conditions in the Hearing Reports, the responsibility of addressing information needs is often attached to the monitoring component of the NIRB IA process.…”
Section: Discussionmentioning
confidence: 99%
“…But this is not unique to the Nunavut's regulatory process. A lack of institutional, community and research capacities in the Arctic (and many other locales) have been identified as limiting factors to meaningful stakeholder and community participation (Fidler & Noble, 2013;McCrank, 2008), and to adaptive management more broadly (Stratos, 2017). Through terms and conditions in the Hearing Reports, the responsibility of addressing information needs is often attached to the monitoring component of the NIRB IA process.…”
Section: Discussionmentioning
confidence: 99%
“…Since most projects and activities do not trigger an IA, few opportunities exist to engage in meaningful discussions about development impacts and regional concerns (Udofia et al, 2017). Regional or strategic assessments can provide better opportunities to address concerns over the appropriateness of different types of development within a region, help communities define the most desirable growth scenarios, and capture those shipping activities that individually and cumulatively affect Arctic environments and communities, but do not necessarily trigger an IA (CCME, 2009;Fidler and Noble, 2013;Noble and Hanna, 2015). There have been some promising developments in the eastern Arctic, including the recent strategic assessment of offshore oil and gas development (NIRB, 2019b); the cumulative effects assessment of shipping across Canada as part of the Oceans Protection Plan (GC, 2018;Lerner, 2018), and the development under the same federal initiative of lowimpact Arctic shipping corridors (see Porta et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nunavut's land-use planning process, which also refers to the marine environment under the Nunavut Agreement, provides a more strategic approach for generating baseline data, defining management objectives, and easing the consultation burden placed on communities (Fidler and Noble, 2013). Currently, however, only one and a half out of three regions in Nunavut are covered under a plan, both of which have not been substantially updated since their approval in 2000 (NPC, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The other major actors in managing the harvest of subsistence resources are the territorial and national governments. Non-Aboriginal appointees sit on the major regional committees and have strong input in decision-making (Department of Indian and Northern Affairs Canada 1984), and the Canadian government maintains jurisdiction over offshore environments in the ISR (Fidler and Noble 2013). Over time, interactions between actor groups have included conflicts over management priorities, the incorporation of indigenous knowledge and practices, and the role of scientific monitoring (Fast et al 2005, Kofinas 2005, Kocho-Schellenberg and Berkes 2015).…”
Section: Nested Hierarchical Organization Of Actor Groupsmentioning
confidence: 99%